Athlete A Documentary Analysis: Breaking the Silence on Harassment and Abuse in Sports - Canan Koca Arıtan; Pinar Ozturk; Mine Kızılgüneş (Pamukkale Spor Bilimleri Dergisi)
Listening to the voices of athletes is important for advancing safe sports and preventing harassment and abuse in sports. This study aims to listen to the voices of athletes of the United States of America (USA) Women's Artistic Gymnastics Team (WAG) against the sexual abuse and organizational neglect they have been exposed to for more than 30 years in order to understand the reasons that lead to abuse. In this context, “Athlete A: The truth behind USA Gymnastics", a Netflix documentary, was analyzed. Analysis was carried out by conducting Baltruschat's “Film Interpretation According to the Documentary Method” process in the Nvivo analysis program. Foucault's concept of biopolitics was utilized to understand the mechanism of power in gymnastics and how this mechanism intervenes in the female athlete's body (on the visible side). The process of proving these behaviors after the athletes broke their silence against organizational negligence and sexual abuse is discussed in the findings section. The case was examined in depth with quotes from the athletes' discourses on the confirmation of the crimes and the healing processes of the athletes after the revealed practices of organizational neglect and sexual abuse. In conclusion, the case of the USA WAG team demonstrates how a culture of silence and failed leadership can lead to complicity and perpetuate harassment and abuse in sports. In order to advance the safe sports, sports organizations need to develop safeguarding policies and procedures that take into account the voices of athletes.